PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN MELALUI WORD OF MOUTH DI SOTO MIE BOGOR PAK KADIR JAKARTA GARDEN CITY - Beata Hessy; Rivera Silitonga (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to evaluate the effect of product quality and brand image on customer satisfaction directly and indirectly through word of mouth. The population sample used as a reference in this subject is 197 respondents using a sampling technique, namely purposive sampling with the criteria of customers who have made purchases at least twice. Data analysis using path analysis techniques (Path Analysis). The results of the analysis show that product quality and brand image variables partially have a significant effect on word of mouth and customer satisfaction, word of mouth variables have a significant effect on customer satisfaction, word of mouth variables mediate the effect of product quality and brand image variables on customer satisfaction.